AKIBAT HUKUM TERHADAP PIHAK YANG TIDAK MELAKSANAKAN PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL DALAM PERKARA ANTARA BURUH DAN PERUSAHAAN - Ellyana Poerwaningsih (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACTThe substance of layoff disputes is complex because one of the possible decisions of the Industrial Relations Court is to order employers to re-employ workers. There is a separate problem if the businessman who is governed does not voluntarily implement the decision of the Industrial Relations Court. The series of procedures for resolving industrial relations disputes conclude with the decision of the Industrial Relations Court. Workers '/ workers' rights cannot be fulfilled because the employer/company still does not want to pay the rights that the worker/worker gets to him, or in other words, do not carry out court satisfaction, this is sometimes due to arrogance due to his defeat or fear of his defeat will cause a lack of authority employers/companies because they have been beaten by workers/workers at these companies.This type of research used in this study is a type of normative legal research, which is a legal research method that uses a statutory approachThe results showed that Parties who did not carry out this case, the company that lost the case could also be reported to the police on the basis of the actions of the employer who did not carry out the court's order (ruling) because the action could be considered as obstructing orders from officials or authorities general as regulated in Article 216 paragraph (1) of the Criminal Code. Parties Not Implementing Industrial Court Decisions In Case, i.e. companies, as the court's decision can be reported to the police on the basis of embezzlement. Because not giving what belongs to another person can be categorized as embezzlement as regulated in Article 372 of the Criminal Code. The decision on the Case of the District Court in the Industrial Relations dispute has permanent legal force, but the company has no good intention to voluntarily implement the contents of the PHI decision. Then there are a number of steps you can take. First, submit a request for execution (seized executorial) to the Court, Second, report the company to the police, Third, file a bankruptcy lawsuit against the companyKeywords: Industrial Relations Disputes, Labor, Companies